Corporate Social Responsibility and Earnings Reports: The Moderating Role of Market Volatility and Trading Opportunities - , Artemis A. Styliadou (Archives of Current Research International, 2024)
This study examines the complex relationship between corporate social responsibility (CSR) and market performance, particularly during quarterly earnings releases for NASDAQ-100 companies. It challenges the notion that ethical companies with strong social performance necessarily offer lower returns. The research explores the concept of "CSR.mv functions" (trading tools based on social responsibility) as a potential way to improve the financial performance of socially responsible investments. Interestingly, the study also finds that companies with lower CSR ratings might offer surprisingly high returns during earnings releases, suggesting unique trading opportunities in this "psychological time." These findings offer valuable insights for the scientific community interested in sustainable investing and the interplay between social responsibility and financial markets. As paper’s main contribution could be considered the study of the relationship between the moderating (independent) variables “market volatility” (MV) and “trading opportunities” (TO) and the (dependent) variable “corporate earnings reports” released by NASDAQ-100 companies in the USA (quarterly), while CSR has been investigated as a dependent variable affecting the above relationship.